Presenteeism: a review of current thinking - Garrow, Valerie (Brighton, 2016)
"As organisations continue to try to achieve more with less, develop leaner systems and greater efficiency, the toll it takes on employees’ mental and physical health has climbed the agenda. Increased presenteeism – employees who attend work whilst ill – is one possible outcome of the pressure on organisations to remain competitive and boost productivity. Macroeconomic studies, carried out principally in North America, Canada and Australia, have attempted to put a dollar value on the cost of presenteeism which, on top of healthcare, also includes a drop in productivity at organisational level and the risk of future health problems for the individual. While there are still some methodological and measurement challenges, the evidence suggests that this is an aspect of organisational life that is worth taking seriously. It seems particularly important to understand the relationship between absenteeism and presenteeism, as organisations drive down the former at the risk of increasing the latter. Organisations may also have concerns that driving down the latter will increase the former. The evidence suggests that presenteeism is both more prevalent than absenteeism, and, unlike sickness absence, is also significantly related to performance. In the long term, presenteeism may also be more damaging for employees’ health, morale and productivity. The promotion of a healthy workplace should therefore drive down both absenteeism and presenteeism, rather than one at the cost of the other. This report is based on an overview of research and current thinking in the field."